Exhaust particle number of a non-road diesel engine fuelled by methyl esters with different fatty acid compositions - Ovaska, Teemu; Niemi, Seppo; Sirviö, Katriina; Nilsson, Olav (Estonian Agricultural University, Faculty of Agronomy, 2019)
The main aim of this study was to find out how methyl esters with different fatty acid compositions affect the exhaust particle numbers. Along with fossil diesel fuel oil (DFO) and renewable diesel (HVO), a high-speed non-road diesel engine was fuelled by rapeseed (RME) and soybean (SME) methyl esters. Particle numbers within the size range of 5.6–560 nm were measured by means of an engine exhaust particle sizer (EEPS). The exhaust smoke, gaseous emissions and the basic engine performance were also determined. During the measurements, the 4-cylinder, turbocharged, intercooled engine was run according to the non-road steady cycle. Methyl esters reduced particles within the size range of 70 to 200 nm. For RME and SME, both positive and significant correlations were found between the sum of the particle numbers detected above the size category of 23 nm and methyl palmitate (C16:0), methyl stearate (C18:0) and methyl linoleate (C18:2) contents at 10% load at rated speed. In terms of nitrogen oxide (NOx) and hydrocarbon (HC) emissions, HVO was beneficial while carbon monoxide (CO) emission was the lowest with DFO. The level in smoke emission was negligible.
Keywords: diesel engine; particle number; methyl ester; fatty acid composition; fi=Energiatekniikka|en=Energy Technology|